Structural insights and cytotoxicity evaluation of benz[e]indole pyrazolyl-substituted amides - Abdul Qaiyum, Ramle; Nadia Nabihah, Mohd Yusof Chan; Ng, Min Phin; Tan, Chun Hoe; Sim, Kae Shin; Tiekink, Edward R. T. *; Fei, Chee Chin (Springer, 2023)
Five new compounds of benz[e]indole pyrazolyl-substituted amides (2a–e) were synthesised in low to good yields via the direct amide-coupling reaction between a pyrazolyl derivative containing a carboxylic acid and several amine substrates. The molecular structures were determined by various spectroscopic methods, such as NMR (1H, 13C and 19F), FT-IR and high-resolution mass spectrometry (HRMS). X-ray crystallographic analysis on the 4-fluorobenzyl derivative (2d) reveals the amide-O atom to reside to the opposite side of the molecule to the pyrazolyl-N and pyrrolyl-N atoms; in the molecular packing, helical chains feature amide-N‒H⋯N(pyrrolyl) hydrogen bonds. Density-functional theory (DFT) at the geometry-optimisation B3LYP/6-31G(d) level on the full series shows general agreement with the experimental structures. While the LUMO in each case is spread over the benz[e]indole pyrazolyl moiety, the HOMO spreads over the halogenated benzo-substituted amide moieties or is localised near the benz[e]indole pyrazolyl moieties. The MTT assay showed that 2e, exhibited the highest toxicity against a human colorectal carcinoma (HCT 116 cell line) without appreciable toxicity towards the normal human colon fibroblast (CCD-18Co cell line). Based on molecular docking calculations, the probable cytotoxic mechanism of 2e is through the DNA minor groove binding.